Clinical practice guidelines for the management of biliary tract cancers 2015: the 2nd English edition. (18th March 2015) - Miyazaki, Masaru; Yoshitomi, Hideyuki; Miyakawa, Shuichi; Uesaka, Katsuhiko; Unno, Michiaki; Endo, Itaru; Ota, Takehiro; Ohtsuka, Masayuki; Kinoshita, Hisafumi; Shimada, Kazuaki; Shimizu, Hiroaki; Tabata, Masami; et al.
Abstract: Background: The Japanese Society of Hepato‐Biliary‐Pancreatic Surgery launched the clinical practice guidelines for the management of biliary tract and ampullary carcinomas in 2008. Novel treatment modalities and handling of clinical issues have been proposed after the publication. New approaches for editing clinical guidelines, such as the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system, also have been introduced for better and clearer grading of recommendations. Methods: Clinical questions (CQs) were proposed in seven topics. Recommendation, grade of recommendation and statement for each CQ were discussed and finalized by evidence‐based approach. Recommendation was graded to grade 1 (strong) and 2 (weak) according to the concept of GRADE system. Results: The 29 CQs covered seven topics: (1) prophylactic treatment, (2) diagnosis, (3) biliary drainage, (4) surgical treatment, (5) chemotherapy, (6) radiation therapy, and (7) pathology. In 27 CQs, 19 recommendations were rated strong and 11 recommendations weak. Each CQ included the statement of how the recommendation was graded. Conclusions: This guideline provides recommendation for important clinical aspects based on evidence. Future collaboration with cancer registry will be a key for assessment of the guidelines and establishment of new evidence. Free full‐text articles and a mobile application of this guideline are available viahttp://www.jshbps.jp/en/guideline/biliary‐tract2.html .